Sudden Tracheal Collapse during EGD and Subsequent Anesthetic Management with Dexmedetomidine-Ketamine in a Patient with Achalasia and Tracheomalacia - Joshua H. Atkins; Jeff E. Mandel; David C. Metz (Case Reports in Anesthesiology)
We present a patient who experienced airway obstruction during an elective esophagogastroduodenoscopy (EGD) under anesthesia secondary to previously undiagnosed tracheomalacia. Physiology of airway obstruction with forced breathing maneuvers is discussed along with the potential advantages of dexmedetomidine-ketamine sedation for management of patients with achalasia undergoing outpatient endoscopic procedures.